A Study of Reduced Graphene Oxide – Cu Nanocomposite for the High Performance Electrochemical Supercapacitor Application: Fabrication and Performance Evaluation (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The modern electrochemical energy storage device, the supercapacitor, has severaladvantageous properties, including high power density, quick charge rates, long-life cycle stability, highspecific capacitance, and low cost. Nanostructured materials, such as metals, metal oxides, andgraphene nanosheets, have been increasingly employed in recent years for energy storage. In this study,nanocomposites of metalmetal-oxide decorated reduced graphene oxide (MMO-rGO) were fabricatedthrough a simple, low-cost chemical reduction process employing hydrazine hydrate as the reducingagent and metal precursors and graphene oxide powder as the starting materials. The three synthesizedrGO-based nanocomposite reported in this study are bismuth oxide decorated rGO (Bi2O3rGO)nanocomposite containing different Bi(NO3)3 concentrations varying from 5mM to 25mM, (ii) silverdecorated rGO (AgrGO) nanocomposite containing 0.5 g AgNO3 and (iii) iron oxide decorated rGO(Fe3O4rGO) nanocomposite with different Fe(NO3)3 content varying from 5mM to 25mM.